PEMIKIRAN HUKUM ISLAM KHALED ABOU EL FADL (UINSI Samarinda, 2015)
This paper discusses the thought of Khaled M. Abou El Fadl about Islamic law. There is an anxiety that is felt by Khaled when he noticed fatwas issued by some fatwas scholars or institutions that exist in the Islamic world. Fatwas are considered to be authoritarian and discriminatory, particularly against women. In addition, these fatwas seem to be rigid; they could not adjust to the demands of the times and conditions. The phenomena of authoritarianism emerged, according to Khaled, due to methodological errors in understanding the legal texts that exist in the Qur'an and Sunnah. Khaled, thus, offers hermeneutic method that consists of three things: text competence, determination of meaning and concept of representation in Islam. When these three elements are met in the determination of the law, Islamic law produced is expected to be authoritative, innovative and dynamic, not authoritarian, discriminative and passive.